Implementasi Teknologi Virtual Reality Sebagai Media Edukasi Mitigasi Bencana Pesisir di Sekolah Dasar Muhammadiyah 9 Kenjeran - Ponidi Ponidi; Lukman Hakim; Holy Ichda Wahyuni; Dede Nasrullah; Nurhidayatullah Romadhon; Uswatun Khasanah; Alfito Deanofal; Abdullah Rasyid Hariyono (Indonesian Journal Publisher, 2025)
Knowledge and preparedness in facing natural disasters is very important, especially for students who are in disaster-prone areas such as the coastal area of ​​Kenjeran, Surabaya. Based on interviews with the principal and teachers at SD Muhammadiyah 9 Surabaya, it is known that the low understanding of students and teachers about disaster mitigation triggers feelings of anxiety and fear about potential disasters that could occur at any time. To overcome this problem, this research implemented Virtual Reality (VR) technology as a medium for disaster mitigation education at SD Muhammadiyah 9 Kenjeran. VR technology was chosen because of its ability to provide a simulation experience that is close to real situations, so it is hoped that it can increase students' and teachers' understanding and resilience in facing crises. This service aims to provide counseling and outreach to teachers and students with VR learning media at SD Muhammadiyah 9 Kenjeran Surabaya. The approach to solving partner problems is to focus on students' understanding of disaster mitigation with VR-based education and the impact of post-disaster psychological problems. The research results show an increase in students' understanding of disaster mitigation measures, as well as an increase in self-confidence in facing disaster threats after implementing VR. Another positive impact is a reduction in students' anxiety and fear levels, which shows that VR-based simulations are effective in preparing students to face emergency situations. The conclusion is that the use of VR technology as a medium for disaster mitigation education can be an effective alternative for increasing students' readiness in facing disasters in coastal areas.